A principal component-guided sparse regression approach for the determination of bitcoin returns - Theodōros Panagiōtidēs; Thanasēs Stengos; Orestis Vravosinos (Journal of Risk and Financial Management, 2020)
We examine the significance of fourty-one potential covariates of bitcoin returns for the period 2010-2018 (2872 daily observations). The recently introduced principal component-guided sparse regression is employed. We reveal that economic policy uncertainty and stock market volatility are among the most important variables for bitcoin. We also trace strong evidence of bubbly bitcoin behavior in the 2017-2018 period.
Keywords: 330; bitcoin; bubble; cryptocurrency; flexible least squares; LASSO; PC-LASSO; principal component; sparse regression